Currency statecraft and de-dollarization: A review article - Francesco Romagnoli (The Journal of European Economic History (JEEH), 2024)
This article explores the dynamics of international currency competition and de-dollarization, focusing on the current dominance of the US dollar and potential challenges from the Chinese renminbi and BRICS countries. It reviews recent literature on currency statecraft, the political economy of the renminbi, and the capacity of BRICS nations to foster de-dollarization. The studies reviewed sug- gest that while no currency or coalition poses an imminent threat to the US dollar's dominance, the geopolitical landscape and countries' foreign policy ambitions play crucial roles in shaping future monetary relations. This review highlights the importance of geopol- itics in understanding the complex interplay of international curren- cies and states' strategic responses.
Keywords: 330